2015
DOI: 10.1007/s10517-015-3043-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis and Electron Microscopy of Glial Cells in the Pancreas of Fetuses and Children

Abstract: Schwann cells forming peri-insular glial sheath of the pancreatic islets in some mammals can be involved in the pathogenesis of diabetes mellitus. Human pancreatic cells contain small elongated or oval cells of unknown origin with S100-immunopositive processes. We found that cells with processes located in pancreatic islets of human fetuses and children are similar to Schwann cells by their morphological and ultrastructural characteristics, immunopositive reaction for S100, and integration with nerve endings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…We found small S100-positive cells with thin processes at the periphery of some islets in humans [37,38]. The same small oval, triangular or elongated cells with long thin processes were observed in the fetal pancreas using electron microscopy [38]. The processes of these cells were often cover or surround nerve fibers passing into islets [38].…”
Section: Structure Of Nic In Human Pancreassupporting
confidence: 69%
See 1 more Smart Citation
“…We found small S100-positive cells with thin processes at the periphery of some islets in humans [37,38]. The same small oval, triangular or elongated cells with long thin processes were observed in the fetal pancreas using electron microscopy [38]. The processes of these cells were often cover or surround nerve fibers passing into islets [38].…”
Section: Structure Of Nic In Human Pancreassupporting
confidence: 69%
“…The same small oval, triangular or elongated cells with long thin processes were observed in the fetal pancreas using electron microscopy [38]. The processes of these cells were often cover or surround nerve fibers passing into islets [38]. In contrast to mice and rats [3,13], these cells were immunonegative to GFAP.…”
Section: Structure Of Nic In Human Pancreasmentioning
confidence: 66%
“…P r o s h c h i n a et al [25] found in humans small S100-reactive cells with thin processes on the periphery of some islets. The processes of these cells often cover or surround the nerve fibres passing to the islets [20,25]. S100-positive cells with thin processes detected by the authors in human pancreas correspond to glial (Schwann) cells observed on the periphery of islets in other mammals [30,33].…”
Section: Discussionmentioning
confidence: 61%